FRET-dependent single/two-channel switch endowing a dual detection for sulfite and its organelle targeting applications. (January 2021) - Huang, Yongfei; Zhang, Yongbin; Huo, Fangjun; Yin, Caixia
Abstract: Förster resonance energy transfer (FRET) is a relatively new strategy for constructing ratiometric fluorescent probes and increasing the Stokes shift. Fluorescent probes based on FRET require spectral overlap between the energy donor emission spectrum and the acceptor absorption spectrum, while providing high energy transfer efficiency. In addition, systems exhibiting FRET typically exhibit intense dual fluorescence, thereby improving the resolution of biological imaging and detection. Herein, on the union of a benzopyrylium salt with a coumarin carboxylic acid, a novel near-infrared fluorescent probe CM-P-DP with FRET regulation strategy was designed and synthesized for the detection of sulfite (SO3 2− ). CM-P-DP showed large Stokes shift (230 nm) and fast response to SO3 2− in pure PBS buffer (15 s). When SO3 2− was added, the fluorescence intensity at 455 nm gradually increased, and the fluorescence intensity at 635 nm decreased rapidly. Moreover, CM-P-DP could effectively target mitochondria and imaging SO3 2− in biological systems. Graphical abstract: Image 1 Highlights: FRET regulation fluorescent detection of SO3 2− was successfully obtained. The probe showed large Stokes shift (230 nm), and fast response to SO3 2− in pure PBS. The probe with excellent performance shows good applications in organelle targeting and in vivo detection.